Utilizing Carbowax-Sulphate Salt in Aqueous Biphasic System for Cd(II) ions Extraction from Produce Water - Sura Jabbar Hussien, Nagam Obaid Kariem, Mohammed jaafar Ali Alatabe (Forest Chemicals Review)
Because of their non-toxicity, durability, and low cost, the application of aqueous Carbowax (PEG) – inorganic salt two-phase systems for the extraction of hazardous metal ions holds a lot of promise. Combining aqueous solutions of certain organic salts with watery arrangements of certain water-soluble polymers (most commonly Carbowax) in specified quantities yields Aqueous biphasic systems. Centrifugation can easily separate the aqueous phases, and the procedure can be performed within the range of experimental variance. The extraction competence of metal ions in such Aqueous biphasic systems is primarily determined by the pH of the salt solution, the concentration of metal ions, the quantity of iodide extractant added, the M.wt of Carbowax and The Aqueous biphasic system’s volume ratio, according to the experimental results. All of these factors will be discussed in this study in order to determine the best experimental conditions for efficient extraction of the potentially toxic heavy metal ion Cadmium (II) in aqueous Carbowax-based two-phase systems. The best condition was 10% (w/w)Carbowax8000 and 10% (w/w) (NH4)2SO4 at pH=2.1 with NaI =0.7 as extraction agents and Vr=0.1 as the optimum condition with extraction efficiency of 90%.